2012
DOI: 10.4149/av_2012_01_63
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus receptor proteins Hsc70 and integrin αvβ3 are located in the lipid microdomains of animal intestinal cells

Abstract: Summary. -Several cell surface molecules such as integrins, sialic acid and Hsc70 have been reported to participate in the process of adsorption and penetration of rotaviruses into cells. Some of them have been found in susceptible cell lines but not in epithelial cells of natural hosts so that their real role in the infection process is unclear. In this study, we attempted to confi rm the presence of Hsc70 and integrin αvβ3 in the cytoplasmic membrane of isolated intestinal epithelial cells of pig, mouse and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…In the present study we did not look for NCL phosphorylation; however, we showed that ␤ 3 Tyr 773 phosphorylation is required for NCL cell surface localization. ␣ v ␤ 3 integrin is found to form a complex with hsc70 in lipid raft microdomains of the cytoplasmatic membrane of susceptible intestinal epithelial cells, and both act as receptors for rotavirus entry (62). Therefore, it is tempting to speculate that ␣ v ␤ 3 and hsc70 may cooperate for cell surface NCL localization and in that case direct or indirect NCL phosphorylation by protein kinase C-and casein kinase 2 may have a role.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we did not look for NCL phosphorylation; however, we showed that ␤ 3 Tyr 773 phosphorylation is required for NCL cell surface localization. ␣ v ␤ 3 integrin is found to form a complex with hsc70 in lipid raft microdomains of the cytoplasmatic membrane of susceptible intestinal epithelial cells, and both act as receptors for rotavirus entry (62). Therefore, it is tempting to speculate that ␣ v ␤ 3 and hsc70 may cooperate for cell surface NCL localization and in that case direct or indirect NCL phosphorylation by protein kinase C-and casein kinase 2 may have a role.…”
Section: Discussionmentioning
confidence: 99%
“…HSP gp96 (HSP90b1), an HSP90 paralogue present in the endoplasmic reticulum of lymphocytes, binds to the aL integrin subunit and maintains cell-surface expression of aL integrins but not a4 integrins [17]. Hsc70 (HSP73) and the integrin avb3 associate together as a complex in lipid raft microdomains of the cytoplasmic membranes of epithelial cells [18]. Extracellular HSP60 specifically binds to the integrin a3b1 expressed by breast carcinoma cells and activates its adhesive function [19].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted with Co-IP followed by protein identification with MS, Hsc70 was found to exist on the plasma membranes of C6/36 and Vero cells (Ren et al, 2007), implying that Hsc70 may be important in receptor-dependent endocytosis. It is further presumed that Hsc70 might be one component of the receptor for rotaviruses infecting animal intestinal cells because Hsc70 levels increase after infection and form a complex with integrin avb3 in the lipid raft microdomains of the cytoplasmic membrane (Guerrero & Moreno, 2012). Since JEV and Hsc70 proteins co-localize and attach to the surface of C6/36 cells, this molecule has been proposed to serve as the receptor for JEV entry into host cells (Ren et al, 2007).…”
Section: Discussionmentioning
confidence: 99%